-22d-3d=2d+d-3d

Simple and best practice solution for -22d-3d=2d+d-3d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -22d-3d=2d+d-3d equation:


Simplifying
-22d + -3d = 2d + d + -3d

Combine like terms: -22d + -3d = -25d
-25d = 2d + d + -3d

Combine like terms: 2d + d = 3d
-25d = 3d + -3d

Combine like terms: 3d + -3d = 0
-25d = 0

Solving
-25d = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Divide each side by '-25'.
d = 0

Simplifying
d = 0

See similar equations:

| 9/8X3/5 | | 1/2x13=9 | | 1+2n+3n=9+4n | | 6x+7=4x+2x | | 2w-4=8 | | 6-10n=36 | | -6i*6i= | | 6C-7=0 | | 2x(4x-5)=20 | | 72=180-2z | | .75x+.5y=1.25 | | 1=6+96x-16x^2 | | m-10=3.3 | | .75y+.5x=1.25 | | 2(x-8)-3x(x+2)=-24 | | 5(3/4x−1)=2x | | 1/2(20-4x)=5x-2 | | .5x+.75y=1.25 | | 1/2x-13=11 | | 1/2x-10=-13 | | 10/31=5w/62 | | 3+m=18 | | 2(6-5d)+2d=20-8d+5 | | (5/6)*c-(2/3)*c=(1/3) | | -7(x-8)+7x=12 | | -g+17=-(g-17) | | 2y+2=24-26 | | w-4.4=9.6 | | 5/6*c-2/3*c=1/3 | | w-4.4=9.7 | | 5c+10=4c-8 | | x-8y=-20 |

Equations solver categories